Trends in utilisation and inequality in the use of reproductive health services in Sub-Saharan Africa - Gordon Abekah-Nkrumah (BMC, 2019)
Abstract Background The paper argues that unlike the income literature, the public health literature has not paid much attention to the distribution of substantial improvements in health outcomes over the last decade or more, especially, in the Sub-Saharan African (SSA) context. Thus, the paper examines current levels of utilisation, changes in utilisation as well as inequality in utilisation of reproductive health services over the last 10 years in SSA. Methods The paper uses two rounds of Demographic and Health Survey (DHS) data from 30 SSA countries (latest round) and 21 countries (earlier round) to compute simple frequencies, cross-tabulated frequencies and concentration indices for health facility deliveries, skilled delivery assistance, 4+ antenatal visits and use of modern contraceptives. Results The results confirm the fact that utilisation of the selected reproductive health services have improved substantially over the last 10 year in several SSA countries. However, current levels of inequality in the use of reproductive health services are high in many countries. Interestingly, Guinea's pro-poor inequality in health facility delivery and skilled attendance at birth changed to pro-rich inequality, with the reverse being true in the case of use of modern contraceptives for Ghana, Malawi and Rawanda. The good news however is that in a lot of countries, the use of reproductive health services has increased while inequality has decreased within the period under study. Conclusion The paper argue that whiles income levels may play a key role in explaining the differences in utilisation and the levels of inequality, indepth studies may be needed to explain the reason for differential improvements and stagnation or deterioration in different countries. In this way, best practices from better performing countries can be documented and adapted by poor performing countries to improve their situation.